Diseño y construcción de una máquina rebanadora de papas Chips. - Casa Toaquiza, Segundo Fernando (2018)
Currently the Cotopaxi province is one of the potatoes main producers in the country, chip potatoes are one of the principal products that are made from this raw material, which is mainly made by small micro-entrepreneurs in the area, the production of this product is used for saling in bus stops and small shops, not having adequate machinery to slice the potatoes, because the existing machines in the market are high cost and industrial use. Taking into account this background this research was made related to potato chips cultivation and production. This research arises from the need having a mechanical, hygienic, easy to operate, resistant and productive tool also that is cheap and simple installation for small businesses in Saquisilí canton. Initially a basic study of the potatoes is carried out, with purpose of knowing the main characteristics of the raw material to obtain potato chips. A chip slicing machine design with a slicing capacity of 150 kg in one hour, with slicing thicknesses ranging from 2 to 3 mm, is carried out. Taking into account that the slicer processed from 4 to 5 in a single sliced.